Principles of Human Rights in Land Procurement for Public Interest (Case Study of Wadas Village Bener Dam) - Muhammad Iqbal Fitra Assegaf; Hana Anisa Dian Pertiwi; Ana Silviana (Budapest International Research and Critics University, 2022)
The regulations on land regulated in UUPA contain a social function, in which every land controlled by the community can be procured for the public interest but must receive balanced compensation. Land acquisition for the public interest has been regulated in Law Number 2 of 2012, the main requirement for land acquisition for the public interest is obtaining a permit. Permits are needed as development legality, but there is an aspect that is no less important, namely the human rights aspect, because land is the primary need of the community so that in granting a land acquisition permit it must reflect the values of human rights. Research approach is a method or method of conducting research. The approach method used in this research is the Socio-legal method using descriptive analytical research specifications, the result of which is to focus on the problems as they were when the research was carried out, then the results of the research were processed and analyzed with the relevant laws and regulations to draw conclusions. , in this case is the case of the construction of the Wadas Village dam which is a national strategic project.